Vestibular Function Change in a Vasopressin-Induced Hydrops Model. Issue 10 (December 2017) - Kim, Minbum; Kim, Kyu-Sung
Abstract : Hypothesis: A vasopressin-induced endoymphatic hydrops model can represent an acute vertiginous attack in Menière's disease (MD). Background: Previous animal models are not appropriate to evaluate the efficacy of new treatments for hydrops because they cannot represent an acute attack of MD. Recently, a new dynamic model was introduced for acute hydrops exacerbation using the vasopressin type 2 receptor agonist, desmopressin (1-deamino-8-D-Arginine vasopressin, VP); however, resulting changes in vestibular function have not been investigated. Methods: A total of 37 guinea pigs were used. Two to 4 weeks after surgical ablation of endolymphatic sacs in 33 guinea pigs, acute exacerbation of hydrops was induced by a single VP injection in 18 animals (group A). Next, two VP injections at 1 hour interval were administered to investigate the effect of multiple VP doses on vestibular function in the other 15 animals (group B). In the remaining four animals, VP was injected without surgery for the control group (control). Bidirectional sinusoidal harmonic acceleration (SHA) tests of vestibular function were performed. "Type I response" was defined as when the maximum slow-phase velocity (SPV) during left rotation (toward the operated ear) was lower than that during right rotation (toward the normal ear). In contrast, "Type II response" was defined as when maximum SPV at the left rotation was higher than that at the right rotation. Vestibular symmetry scores were analyzed at baseline and after each of two VP injections given 1 hour apart. Results: Vestibular symmetry scores increased at 1 hour after VP injection in all 18 animals in group A ( p < 0.001). Two hours after VP injection, symmetry score decreased to the initial score. Two different types of vestibular response were observed after VP. However, the symmetry scores between type I and II responses were not significantly different ( p = 0.173). In all 15 animals of Group B, vestibular asymmetry was sustained over 3 hours when two VP injections were given 1 hour apart. In three of Group B, the type of vestibular response changed from type II response to type I response after the 2nd VP injection; however, no animal demonstrated a shift from type I to type II response. Conclusion: VP can transiently induce an acute exacerbation of hydrops and asymmetric vestibular dysfunction in guinea pigs. This model could help in studying new treatments for acute hydrops and in explaining the mechanism of bidirectional nystagmus in MD. Abstract : Supplemental Digital Content is available in the text